Optimisation and Application of a Novel Method to Identify Bacteriophages in Maternal Milk and Infant Stool Identifies Host-Phage Communities Within Preterm Infant Gut - Young, Gregory R.; Yew, Wen C.; Nelson, Andrew; Bridge, Simon H.; Berrington, Janet E.; Embleton, Nicholas D.; Smith, Darren L. (Frontiers in Pediatrics, 2022)
Human milk oligosaccharides, proteins, such as lactoferrin, and bacteria represent just some of the bioactive components of mother's breast milk (BM). Bacteriophages (viruses that infect bacteria) are an often-overlooked component of BM that can cause major changes in microbial composition and metabolism. BM bacteriophage composition has been explored in term and healthy infants, suggesting vertical transmission of bacteriophages occurs between mothers and their infants. Several important differences between term and very preterm infants (<30 weeks gestational age) may limit this phenomenon in the latter. To better understand the link between BM bacteriophages and gut microbiomes of very preterm infants in health and disease, standardised protocols are required for isolation and characterisation from BM. In this study, we use isolated nucleic acid content, bacteriophage richness and Shannon diversity to validate several parameters applicable during bacteriophage isolation from precious BM samples. Parameters validated include sample volume required; centrifugal sedimentation of microbes; hydrolysis of milk samples with digestive enzymes; induction of temperate bacteriophages and concentration/purification of isolated bacteriophage particles in donor milk (DM). Our optimised method enables characterisation of bacteriophages from as little as 0.1 mL BM. We identify viral families that were exclusively identified with the inclusion of induction of temperate bacteriophages (Inoviridae) and hydrolysis of milk lipid processes (Iridoviridae and Baculoviridae). Once applied to a small clinical cohort we demonstrate the vertical transmission of bacteriophages from mothers BM to the gut of very preterm infants at the species level. This optimised method will enable future research characterising the bacteriophage composition of BM in very preterm infants to determine their clinical relevance in the development of a healthy preterm infant gut microbiome.